Pengembangan Sistem Informasi Pengiriman Kendaraan Bermotor dan Alat Berat berbasis Web (Studi Kasus: CV. Arsa Jaya Mandiri) - Arya Rizky Sandi; Fajar Pradana; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
CV. Arsa Jaya Mandiri is a freight forwarding company for cars, motorcycles, trucks and heavy equipment. The process of managing data on the CV. Arsa Jaya Mandiri is carried out conventionally, such as income and expenses, which are carried out in a transaction book. Recording done in this way tends to be bad in terms of data security, and according to the company, there have been several errors in the calculation process during the recapitulation in preparing income and expenditure reports. Access to information about the company is still limited to outsiders, such as information about shipping costs and the company in general. Based on the issues raised, an information system was created to address data management issues and facilitate access to delivery information by the company's external parties. The waterfall method and the Laravel framework are used in the development of information systems. After system implementation, validation testing is carried out with black-box testing with a valid value of 100%, which states that the specified requirement specifications are appropriate. Usability testing as measured by the System Usability Scale (SUS) shows a final score of 78 for the developed system. This states that the information system is in the acceptable category with a grade of C, which has good adjective ratings.